Government expenditure and inflation (Empirical study using Granger causality in Indonesia 2000-2021) (Asian Journal of Economics and Business Management, 2023)
A Government expenditure is one of important things in determine the economic performance of the country, but when it comes to increasing the economic growth, it can cause inflation. The high inflation rate will impact in economics of the nation as a whole. This study aims to investigate the casual relationship between government expenditure and inflation rate in Indonesia during 2000-2021 period. Time series data obtained from the official website of Central Bureau of Statistics of Indonesia and the Finance Ministry of Indonesia is analyzed using Granger Causality Test. The result show that the variables are stationery and have long run relationship. However, they only have one-way relationship in which government expenditure cause inflation rate but inflation rate doesn’t cause government expenditure in Indonesia. We suggest appropriate fiscal-monetary policy mix, redirecting government expenditure to productive sector and maintained strategic in controlling inflation rate.